FTIR SPECTROSCOPY OF OH IN OLIVINE: A NEW TOOL IN KIMBERLITE EXPLORATION - Matveev S.; Stachel T. (My University, 2007)
Our study of olivines from Canadian kimberlites shows that the application of FTIR spectroscopy significantly improves the reliability of olivine as a kimberlite indicator mineral (KIM). We have developed an algorithm that yields the water concentration and the normalized intensity of the OH IR absorption band at 3572 cm-1 from unpolished olivine grains of unknown thickness. For 80% of kimberlitic olivines these two parameters are significantly higher than those for olivines from non-kimberlitic magmas and consequently, olivines with water concentrations >60 ppm and a strong absorption band at 3572 cm-1 can be reliably classified as being kimberlitic. We have identified two major spectral features in the OH absorption bands of kimberlitic olivines that allow for a more detailed classification: (a) the presence of three types of high-requency OH absorption bands (Group 1A, 1B and 1C) and (b) the proportion of low-frequency OH absorption bands (Group 2) relative to high-frequency bands (Group 1). Comparison of our results with experimental studies suggests that differences within Group 1 OH absorption bands are due to different pressures of crystallization or hydrogenation. The three identified types of Group 1 OH absorption bands approximately correspond to high (P > 2 GPa, Group 1A), moderate (2-1 GPa, Group 1B), and low (<1 gpa, group 1c) pressures of hydrogenation. 2 oh ir absorption bands in olivines with nio> 3500 ppm are interpreted to reflect olivine-orthopyroxene equilibria and hence are indicative of xenocrystic olivine derived from lherzolitic or harzburgitic mantle sources. Interaction of xenocrystic olivine with hydrous kimberlitic melts with low silica activity likely will cause a gradual increase in Group 1 absorption bands. Therefore, FTIR spectra of olivine can be used to obtain qualitative estimates of the duration of interaction between mantle material and a kimberlitic melt. In addition to applications in kimberlite and diamond exploration, FTIR spectra of olivine phenocrysts, combined with mineral chemical data, may also provide insights into kimberlite evolution. Our data suggest that in some instances the ascent of kimberlitic magmas could have been interrupted at or near the Moho, followed by olivine crystallization and exsolution of aqueous fluids. © 2007 Elsevier Ltd. All rights reserved.
Keywords: olivine; kimberlite